Patrons, clients, and empire chieftaincy and over-rule in Asia, Africa and the Pacific - Newbury, C. W. (Colin Walter), 1929- (Oxford University Press, 2003)
This is a wide-ranging comparative study of relationships between the indigenous leadership of traditional states and colonizing Europeans from the 17th to the 20th century.